Simulation of corrected mass flow and non-adiabatic efficiency on a turbocharger - Mohd Ibthisham, A. (2013)
The aim of this project is to evaluate turbine's performance based on its actual condition. Holset H3B nozzles turbine geometry was used as the simulation model. Turbine's actual working condition was simulated using finite volume method (FVM). Three-dimensional Navier-Stoke equations with heat convection loss via turbine volute are solved. The parameters studied are corrected mass flow and turbine's efficiency at different heat transfer coefficients. Temperature difference within turbine's volute is the major factor that deteriorates turbine's efficiency. It is found that the higher the heat transfer coefficient, the lower turbine's efficiency will be.